Glutamic acid-assisted synthesis of zinc-doped hydroxyapatite porous microspheres. (November 2020) - Qi, Mei-li; Mei, Fengce; Cui, Fengkun; Qi, Mei-li; Qi, Liang
Abstract: Zinc plays a crucial role in human bone metabolism. In the present study, zinc-doped hydroxyapatite (Zn-HA) porous microspheres were environment-friendly synthesized through a hydrothermal homogeneous precipitation route by using glutamic acid as the growth regulator. FE-SEM results show that Zn-HA microspheres consist of nanosheets and exhibit relatively uniform spherical morphology with porous and petal-like structure. EDS mapping indicates a homogeneous Zn distribution on the microsphere. The one-step process employed to realize zinc doping in the HA porous microspheres offers a functional route to obtain a green Zn-HA product of considerable potential in multiple fields, such as drug-controlled release matrix, injectable bone defect fillers, delivery carriers for proteins and genes.